Performance improvement through optimal location and sizing of distributed generation / Zuhaila Mat Yasin - Mat Yasin, Zuhaila (Institute of Graduate Studies, UiTM, 2014)
This thesis presents a new technique to determine the optimal locations and sizing of multiple DG units in a distribution system based on the concepts and principles of quantum mechanics in the Evolutionary Programming (EP) namely Quantum-Inspired Evolutionary Programming (QIEP). The concept of Quantum- Inspired is implemented according to three levels namely quantum individuals, quantum groups and quantum global in order to accelerate the convergence time of the EP. To enhance the robustness of the algorithm, the QIEP technique is constructed based on multiobjective model in which the multiobjective functions consist of reducing power losses, increasing maximum loadability and cost minimisation. All simulations in this study were carried out using IEEE 69-bus distribution test system and 141-bus distribution test system.